Pertanggung Jawaban Tindak Pidana terhadap Pelaku Pengedaran Obat Tanpa Izin Edar : (Studi Kasus Putusan PN Mataram No.:111/pid.B/2013/PN.Mtr) - Firnawati Firnawati; Ahmad Yunus (Lembaga Pengembangan Kinerja Dosen, 2024)
Circulating drugs without a distribution permit is a criminal act, where the drugs being distributed are not necessarily relevant to their composition and manufacture. This means that the safety, efficacy and benefits of drugs being traded are not guaranteed. Then the perpetrators of distributing drugs without a distribution permit will be punished and subject to criminal penalties. In this case Law no. 17 of 2023 concerning Health regulates criminal provisions for perpetrators of distributing drugs without a distribution permit with a prison sentence of 12 years and a fine of five billion rupiah, but the criminal sanctions imposed by the judge in decision case number 111/pid.B/2013/PN/ are reduced. Mtr does not provide a deterrent effect for perpetrators. The problems in this research are: first, what is the responsibility for perpetrators of criminal acts of distributing drugs without a distribution permit? Second, what are the judge's considerations in handing down a decision regarding the distribution of drugs without a distribution permit in case number 111/pid.B/2013/PN/Mtr?The results of this research are to show that the form of responsibility of the defendant is in accordance with the elements of responsibility, because the actions carried out by the defendant contained an element of intentional error and the judge sentenced the defendant to 10 months' imprisonment, which according to the author was not appropriate because the sentence This will not have a deterrent effect on the perpetrator.